2015
DOI: 10.1016/j.ntt.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal cocaine exposure on early postnatal rodent brain structure and diffusion properties

Abstract: Prenatal cocaine exposure has been associated with numerous behavioral phenotypes in clinical populations, including impulsivity, reduced attention, alterations in social behaviors, and delayed language and sensory-motor development. Detecting associated changes in brain structure in these populations has proven difficult, and results have been inconclusive and inconsistent. Due to their more controlled designs, animal models may shed light on the neuroanatomical changes caused by prenatal cocaine; however, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Use of model organisms allows carefully controlled administration of the cocaine to pregnant mothers and detailed analysis of cellular and molecular abnormalities associated with in utero drug exposure [ 11 , 12 , 13 , 14 ]. Decreased brain size has been demonstrated in rodents and monkeys treated with cocaine in utero [ 11 , 14 , 15 , 16 ]. Mice raised after in utero cocaine exposure have behavioral deficits [ 12 ] and acquire cocaine self-administration more quickly than untreated controls [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Use of model organisms allows carefully controlled administration of the cocaine to pregnant mothers and detailed analysis of cellular and molecular abnormalities associated with in utero drug exposure [ 11 , 12 , 13 , 14 ]. Decreased brain size has been demonstrated in rodents and monkeys treated with cocaine in utero [ 11 , 14 , 15 , 16 ]. Mice raised after in utero cocaine exposure have behavioral deficits [ 12 ] and acquire cocaine self-administration more quickly than untreated controls [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the outcomes of the clinical studies of Rivkin et al (2008) and Grewen et al (2014), McMurray et al (2015 did not observe differences in total brain volume or in cortical regions in their latest experimental study of rats. These authors found, however, alterations in fractional anisotropy in regions that were associated with emotional regulation and reward processing.…”
Section: Clinical Manifestations Structural Abnormalitiesmentioning
confidence: 56%
“…Species-specific differences may account for the variation in outcomes observed in this study compared to the study of Grewen et al (2014) and McMurray et al (2015).…”
Section: Clinical Manifestations Structural Abnormalitiesmentioning
confidence: 74%
“…Rats in the CC group were given twice daily injections of 15 mg/kg (s.c.) cocaine hydrochloride (Sigma, St. Louis, MO; dissolved in normal saline) at approximately 09:00 and 16:00 h, while UN rats were given no injections but were weighed and handled daily, as previously described (McMurray et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…The 2013 National Survey on Drug Use and Health found that 5.4% of pregnant women in the US were using illicit drugs, including cocaine (SAMHSA 2014). Affecting both mother and fetus, prenatal cocaine use has linked to deficits in infant development and maternal care in humans (Burns et al, 1991; Kelley et al, 1991; Murphy et al, 1991; Williams-Petersen et al, 1994; Mayes et al, 1997; Strathearn and Mayes 2010; Rutherford et al, 2011; Cain et al, 2013; Liu et al, 2013; Chiriboga et al, 2014; Grewen et al, 2014) and in rats (Johns et al, 2005; McMurray et al, 2013; Zeskind et al, 2014; McMurray et al, 2015; Lippard et al, 2015). As cocaine targets monoamine transporters, including the dopamine transporter, phasic dopamine transmission in cocaine-exposed mothers may be compromised.…”
Section: Introductionmentioning
confidence: 99%